2018
DOI: 10.3747/co.25.3916
|View full text |Cite
|
Sign up to set email alerts
|

Completing the Cervical Screening Pathway: Factors that Facilitate the Increase of Self-Collection Uptake among Under-Screened and Never-Screened Women, an Australian Pilot Study

Abstract: A well-implemented process, led by trusted, knowledgeable, and engaged health care professionals who can provide appropriate support and information, can assist under-screened and never-screened women to complete the hpv self-collection pathway successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(81 citation statements)
references
References 16 publications
7
74
0
Order By: Relevance
“…29 Five studies employed a multimethod or mixed methods design. 47 67–70 A total of 58 studies employed a quantitative approach: 47 cross-sectional studies, 41–46 48 50–63 65 66 71–94 two pre–post surveys, 64 95 eight RCTs 33–40 and one prospective cohort. 49 Quantitative studies examined a wide range of end users, including underscreened and vulnerable subpopulations such as women living HIV, 51 60 61 transmales 62 and female sex workers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Five studies employed a multimethod or mixed methods design. 47 67–70 A total of 58 studies employed a quantitative approach: 47 cross-sectional studies, 41–46 48 50–63 65 66 71–94 two pre–post surveys, 64 95 eight RCTs 33–40 and one prospective cohort. 49 Quantitative studies examined a wide range of end users, including underscreened and vulnerable subpopulations such as women living HIV, 51 60 61 transmales 62 and female sex workers.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies suggested strategies to increase end user’s confidence in performing self-sampling correctly. 47 55 70 In clinical settings, end users cited the important role of a trusted healthcare provider in fielding questions and providing reassurance that sampling was done correctly. 27 30 47 70 In addition, clear, step-by-step instructions with illustrations in the appropriate language were suggested as methods to facilitate self-sampling and improve end users’ confidence.…”
Section: Resultsmentioning
confidence: 99%
“…Primary care providers could verify the screening status of their patients belonging to the target screening population and offer self sampling kits to those who have not been screened recently. 129 130 Primary care providers could be an effective alternative in settings where mailing sampling kits as part of an organized screening program is not feasible and door-to-door invitation is too costly. Self sampling could also become the new paradigm for primary cervical cancer screening in the general population as an alternative for the collection of a clinician sample.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn negatively affected their confidence in explaining the NCSP changes to women and potentially missed opportunities for cervical screening via self‐collection. A growing body of evidence demonstrates the potential for self‐collection to overcome barriers to clinician‐collected cervical screening and improve participation in Australia 26-28 and among Indigenous women in Aotearoa New Zealand and Canada 29-31 . Currently, there are only two laboratories in Australia that support analysis of self‐collected samples 32 .…”
Section: Discussionmentioning
confidence: 99%